Studies of historical earthquakes in Southern Poland : Outer Western Carpathian Earthquake of December 3, 1786, and first macroseismic maps in 1858-1901 /: Outer Western Carpathian Earthquake of December 3, 1786, and first macroseismic maps in 1858-1901. (2015) - Unknown
No abstract available